Communicating recent customers’ decisions to strategic customers of a service system: the join or balk dilemma - Economou, Antonis (International Conference on Business and Economics - Hellenic Open University, 2025)
In the present paper, we consider the fundamental model of Rational Queueing which concerns the join-or-balk dilemma of homogeneous strategic customers at the single-server Markovian queue with infinite waiting space. This model has been extensively studied under various assumptions regarding the information that is available to the customers upon arrival. The information assumptions that have appeared in the literature deal mainly with the possibility of the customers to observe the queue length before making their decisions (observable model, unobservable model, partially observable model, observable with delay model etc.). In the present paper, we introduce a new class of models where the information that is communicated to the arriving customers concerns the recent customers’ decisions. We present various models that belong to this class and report some preliminary promising results that show that this kind of information is valuable and can lead to good outcomes. JEL Classifications: C690, C720 Keywords: service systems, queueing, strategic customers, equilibrium customer strategies, information